2020
DOI: 10.1002/pan3.10089
|View full text |Cite
|
Sign up to set email alerts
|

Environmental aesthetics: A synthetic review

Abstract: Environmental aesthetics has emerged in the last 50 years from the philosophical fields of aesthetics and environmental philosophy. The questions and issues which shape this subfield have been drawn principally from the Western philosophical tradition. Other disciplinary perspectives have also shaped environmental aesthetics, including landscape architecture, human geography, restoration ecology and empirical studies on landscape preferences in developmental and environmental psychology. This review and synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 103 publications
2
27
0
Order By: Relevance
“…Another phase in this study involved informed participants and their reported experience(s) of ugliness. It showed that ugliness triggered a myriad of meanings, seeping through psychoanalysis and folk psychology to semiotics and philosophy (Bayley, 2012; Brady, 2020; Eco, 2007; Hagman, 2003; Küplen, 2011; Wenzel, 1999). Their observations nested roughly into the meanings of ugliness posited by Henderson (1966): sensory, moral, visceral and adjudicative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another phase in this study involved informed participants and their reported experience(s) of ugliness. It showed that ugliness triggered a myriad of meanings, seeping through psychoanalysis and folk psychology to semiotics and philosophy (Bayley, 2012; Brady, 2020; Eco, 2007; Hagman, 2003; Küplen, 2011; Wenzel, 1999). Their observations nested roughly into the meanings of ugliness posited by Henderson (1966): sensory, moral, visceral and adjudicative.…”
Section: Discussionmentioning
confidence: 99%
“…punk), as well as the environment (e.g. arid volcanic landscapes) (Brady, 2020; Cook & Furnham, 2012; Goldman & Waymer, 2014; Kieran, 1997). The experience of ugliness also seems distinct from that of beauty in evolutionary and emotional terms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the field has continually expanded its scope, its connections with environmental ethics (i.e. whether and to what extent aesthetic appreciation of the natural environment may support relevant moral attitudes) have drawn much attention from environmental philosophers (Brady and Prior, 2020). For example, it is contended that the care and respect for nature can be grounded in and facilitated by the discovery of natural beauty (Hargrove, 1989; Rolston, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interest in the esthetic appreciation of natural environments was renewed in the twentiethcentury following Hepburn's essay and positive esthetics emerged, which consider nature as essentially beautiful insofar as it is untouched by humans. Nowadays the debate revolves around cognitive and non-cognitive views [18].…”
Section: Introductionmentioning
confidence: 99%